Learning democracy in Japan - Thomas, J. E. (Beverly Hills, 1985)
There are few countries in the world where adult education has played a more important role in shaping a democratic society than in Japan during the post-war era. This first account in English of the evolution of adult education is presented in the context of Japan's often turbulent history and periods of social upheaval. Professor Thomas describes the rich range of current provision for adult education, and analyses its relationship to social and political changes in Japan: in particular, the role that adult education played in 1945 in helping Japan to adjust to a world from which it had excluded itself for years. This highly readable book examines such important issues as the role of adult 'social' education in Japan's economic success and explores its contribution to Japanese political awareness.